An update on incisional hernias - Rico, Omar González; Solís, Luis Fernando Pérez; Rodríguez, Jesús Eduardo Trujillo; García, Elias John; Páez, María Fernanda Vázquez; Castro, Karen Alicia Hernández; Cambrón, Mayel Ortega; Hidalgo, José Alejandro Cano (International Surgery Journal, 2024)
After abdominal surgery, incisional hernias are a common occurrence that may occur, and the frequency of these hernias may vary considerably depending on a number of different circumstances. This article presents a comprehensive analysis of the characteristics of incisional hernias, including their occurrence, causes, potential complications, and treatment options. Therefore, it is essential for healthcare providers to have a comprehensive understanding of these aspects in order to provide effective treatment and reduce the negative effects of this condition on patients.